A survey on burnout and depression risk among anaesthetists during COVID-19: the tip of an iceberg? - Samuel Ern Hung, Tsan; Anand, Kamalanathan; C K, Lee; S A, Zakaria; Chew Yin, Wang (John Wiley & Sons, Inc., 2020)
The recent article by Heath et al. [1] is a timely one, which addresses the need for solutions to minimise the adverse psychological impact of the COVID-19 pandemic. In the midst of this public health crisis, anaesthetists are at the frontline of the ‘war’ against the virus, and hence at great risk of suffering from mental and emotional harm, akin to a ‘parallel pandemic’ [2]. Due to the nature of the work of anaesthetists in managing patients in acute and critical care, with special emphasis on airway management and ventilatory support, their work-load worldwide has increased during the pandemic, predisposing to burnout. Also, as the clinicians responsible for airway management, anaesthetists are among those at greatest risk of contracting COVID-19 [3], and with this risk comes worry and anxiety, contributing to further psychological distress. In view of the multiple psychological challenges faced by anaesthetists worldwide, we sought to define the problem by investigating the prevalence of burnout and depression risk among anaesthetists in a nationally designated exclusive COVID-19 hospital.